A balloon for Isabel - Underwood, Deborah; Rankin, Laura (New York, NY : Greenwillow Books, 2010)
As graduation day approaches, Isabel tries to convince her teacher that she and Walter, both porcupines, should receive balloons on the big day just like the other children.
A Junior Library Guild selection
Ages 3-7.
Keywords: Porcupines -- Juvenile fiction; Balloons -- Juvenile fiction; Schools -- Juvenile fiction; Commencement ceremonies -- Juvenile fiction; Candy -- Juvenile fiction; Porcupines -- Fiction; Balloons -- Fiction; Schools -- Fiction; Graduation (School) -- Fiction; Candy -- Fiction; Picture books